Analisis Penggunaan Sistem Informasi Perpustakaan pada Layanan Peminjaman Buku di Dinas Perpustakaan dan Kearsipan Sidoarjo - Elza Endang Setiowati; Ahmad Yusroni (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Digital transformation through the Electronic-Based Government Sistem (SPBE) requires public institutions to optimize services through information sistems, yet technical obstacles are frequently encountered in practice. This study aims to analyze the implementation of the INLISLite application in book lending services at the Sidoarjo Library and Archives Service and to identify barriers to data integration between the head office and outdoor services. The research method employed is descriptive qualitative, with data collection techniques involving observation, in-depth interviews, and documentation. The results indicate that while the implementation of INLISLite has improved circulation efficiency at the head office, mobile library services still face significant constraints due to limited internet connectivity. This condition forces field officers to rely on manual recording, which triggers a double-entry data phenomenon upon returning to the head office, thereby delaying real-time book stock synchronization and increasing the risk of human error. In conclusion, the effectiveness of the information sistem has not yet reached all service units harmoniously. The researcher suggests the need to strengthen network infrastructure in mobile library operational areas and to develop sistem modules that support periodic data synchronization modes to ensure data accountability and more responsive public service quality in Sidoarjo Regency.